Rheumatoid arthritis in minorities. (2013)
Latin America and the Caribbean (LAC) is a rapidly growing region with almost 600 million inhabitants composed of Mexico, Central and South America, and the islands of the Caribbean [1, 2]. The Americas were first inhabited by people crossing the Bering Land Bridge from northeast Asia into Alaska well over 10,000 years ago. Native Americans descend from at least three streams of Asian gene flow [3]. Europeans arrived after 1492 following Christopher Columbus’s voyages. African people were captured and taken to America by the transatlantic slave trade from the 16th to the 19th centuries. Hence, the population of LAC comprises a variety of ancestries, ethnic groups, and races, making the region one of the most diverse in the world. The specific composition varies from country to country: many have a predominance of European-Native American, or Mestizo, population; in others, Native Americans are a majority; some are dominated by inhabitants of European ancestry; some countries’ populations are primarily Mulatto [4]. To a less extent, Black, Asian, and Zambo (mixed Black and Native American) are also identified regularly [4]. Noteworthy, ethnic self-identification is culturally and biologically complex and is not correlated with self-reported ancestry which should be no longer evaluated by questionnaire but rather by the use of ancestry informative markers (AIMs) at the molecular level